2017
DOI: 10.4236/psych.2017.813141
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors at Work and Occupational Stress in Gas Station Attendants in Ecuador

Abstract: The aim was to determine the association between the psychosocial factors at work and occupational stress in gas station attendants in Ecuador. A transversal study was conducted, including 146 dispatchers of petroleum-derived products. The participants answer a sociodemographic data, the Instrumento de Factores Psicosociales en el Trabajo (Survey of Psychosocial Factors at Work) and the Cuestionario de Evaluación del Estrés (Stress Evaluation Survey). The mean age was of 30.05 years (SD = 8.31), being 67.7% ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Liu et al conducted occupational health examinations and used anxiety questionnaires to investigate the sleep and emotional statuses of gas station operators and managers [54]. To study stress levels in gas station employees, all questionnaires used to conduct surveys were retrieved in the literature, such as the Cuestionario de Evaluación del Estrés (Stress Evaluation Survey), a modified Stress Diagnostic Survey (SDS) questionnaire, and a self-made questionnaire [49][50][51].…”
Section: Measurement Methods Used In the Retrieved Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al conducted occupational health examinations and used anxiety questionnaires to investigate the sleep and emotional statuses of gas station operators and managers [54]. To study stress levels in gas station employees, all questionnaires used to conduct surveys were retrieved in the literature, such as the Cuestionario de Evaluación del Estrés (Stress Evaluation Survey), a modified Stress Diagnostic Survey (SDS) questionnaire, and a self-made questionnaire [49][50][51].…”
Section: Measurement Methods Used In the Retrieved Literaturementioning
confidence: 99%
“…For some employees, the tasks include sales promotion and addressing customer complaints, which confers even greater pressure. Pérez et al evaluated various symptoms related to occupational stress in a group of gas station employees and found higher reports of psycho-emotional symptoms, with >70% of participants mentioning a "very high" frequency [49]. This suggests that the employees might have experienced significant stress at work.…”
Section: Workload and Stress Problemmentioning
confidence: 99%
“…Additionally, these outcomes concurred with ELsayed et al, (2018) (1) who conducted study under title of occupational hazards among gas station workers in Egypt and they demonstrated that of the workers in the study, over one third (35.8%) were between the ages of 20 and 30. Moreover, Alb´an-P´erez et al, (2017) (22) who carried a study in Ecuador to investigate the psychosocial factors at work and occupational stress in gas station attendants and they reported that the mean age was of 30.05 years (SD= 8.31). Furthermore, these outcomes were inconsistent with OE and QM, (2018) (24) who conducted a study to assess the occupational hazards, health problems and safety practices of petrol station attendants in Nigeria and they noticed that the mean age of respondents was 24.3 ± 4.6 years.…”
Section: Table (1)mentioning
confidence: 99%
“…Increasing job demands and interaction with customers derived from ferocious market competition between fuel companies favor a rise in worker responsibilities. Besides, constant change in work conditions implies new workloads for workers [ 51 ]. Work overload destroys workers’ environment-coping competencies, which may produce emotional changes and symptoms of stress such as anxiety, irritability, sadness and depression, which is identified as a psychological and social risk factor [ 4 ].…”
Section: Literature Review and Conceptual Paradigmmentioning
confidence: 99%
“…Remuneration is one such psychosocial factor that leads to negative emotions in workers, mostly relating to dissatisfaction with the balance between expected work effort and the reward. Several studies have pointed out that the disparity between these job features is a psychosocial risk factor leading to other problems such as fatigue and burnout [ 51 ].…”
Section: Literature Review and Conceptual Paradigmmentioning
confidence: 99%